Metode Penelitian Hukum Normatif : Bagaimana? - Rusli, Hardijan (Pelita Harapan University, 2006)
Prof Dr. C.F.G. Sunaryati Hartono, in conclusion of her research conducted in 1982, concluded that legal scientists and lawyers in Indonesia seem neglect and lack of knowledge of legal research methods. This condition does not change much until now because it can be seen from papers of undergraduate law students in Indonesia. Many of the papers stated that the methods used in the papers are Normative Legal Research. But if we check in the papers it seems that the Normative Legal Research methods is nothing but using the secondary (library) data. The students only know that normative legal research is using secondary (library) data not primary data. Is it normative legal research? So what or how is actually normative legal research? What can we expect from law students if the legal scientists and lawyers themselves do not know what or how normative legal research is? This article tries to find solution of the problem that can be useful for knowledge of legal research methods in Indonesia.